1995
DOI: 10.1111/j.1365-2249.1995.tb03721.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating antiinflammatory cytokine IL-10 in patients with inflammatory bowel disease (IBD)

Abstract: SUMMARY IBD is characterized by increased serum concentrations of different cytokines. IL‐10 inhibits the production of proinflammatory cytokines such as IL‐1, tumour necrosis factor‐alpha (TNF‐a), interferon‐gamma (IFN‐γ) and IL‐6 through inhibitory action on Th1 cells and macrophages, and it is thought to be a suppressor type cytokine. In the present study we determined serum concentrations of IL‐10 in patients with ulcerative colitis (UC) and Crohn's disease (CD). We measured human IL‐10 by our own newly es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(65 citation statements)
references
References 32 publications
(17 reference statements)
5
58
2
Order By: Relevance
“…IL-10 is constitutively expressed in normal gut tissue, and inhibits the production of inflammatory cytokines, however, it is also produced by activated macrophages (Fiorentino et al, 1991). Our results support previous observations of elevated levels of IL-10 in IBD patients as a response to chronic inflammation (Kucharzik et al, 1995), and it has been suggested that despite its up-regulation, the intrinsic intestinal bioavailability of IL-10 might be insufficient to control the local inflammation (Autschbach et al, 1998). The increased IL-10 levels observed in the Pos animals may be indicative of a state of ongoing inflammation, whereas EWP treatment accelerated healing, reduced inflammation and returned IL-10 to levels similar to those of Neg animals.…”
Section: Effect Of Ewp On Local Cytokine Expressionsupporting
confidence: 93%
“…IL-10 is constitutively expressed in normal gut tissue, and inhibits the production of inflammatory cytokines, however, it is also produced by activated macrophages (Fiorentino et al, 1991). Our results support previous observations of elevated levels of IL-10 in IBD patients as a response to chronic inflammation (Kucharzik et al, 1995), and it has been suggested that despite its up-regulation, the intrinsic intestinal bioavailability of IL-10 might be insufficient to control the local inflammation (Autschbach et al, 1998). The increased IL-10 levels observed in the Pos animals may be indicative of a state of ongoing inflammation, whereas EWP treatment accelerated healing, reduced inflammation and returned IL-10 to levels similar to those of Neg animals.…”
Section: Effect Of Ewp On Local Cytokine Expressionsupporting
confidence: 93%
“…9 and Y. Cong, personal communication). Whereas IL-10 knockout mice provide an excellent model to study CD pathogenesis, particularly its microbial aspects, human genetic variations known to date as associated with CD do not include the IL-10 locus and serum IL-10 concentrations are increased in the acute phase of CD (26). Therefore, the data presented here should not be considered as definitive evidence against the use of curcumin in CD patients.…”
Section: Discussionmentioning
confidence: 88%
“…Basal levels of IL-10 are likely to modulate the production of other proinflammatory mediators and thus subtle differences in basal levels of IL-10 may affect the steady-state cytokine network. Kucharzik et al observed an increased serum IL-10 concentration in patients with CD and UC compared with controls [22]. However, only patients with active CD and active UC presented with significantly increased IL-10 serum levels, whereas patients with inactive disease did not exhibit any significant increase.…”
Section: Discussionmentioning
confidence: 92%